Comparison of Weight Gain in Injectable Contraceptive 1-Month And 3-Month Acceptors at The Independent Midwife Practice Tambaksari Surabaya - Ardiani, Khoiriya; Nursucahyo, Eko; Prijambodo, Tjatur; Anas, Muhammad (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2020)
Background: Injectable contraception is the most widely used type of contraception by Indonesian mothers because of its effective way of working, practical use, and lower price. However, in the use of injectable contraception, there are side effects, one of which is weight gain.Objective: To find out the differences in weight gain for 1-month and 3-months of injecting contraceptive acceptors.Method: This was an analytical observational study with a cross-sectional design. This research was conducted at the Independent Practice Midwife of Sri Retnaningtyas, Tambaksari District, Surabaya. The total sample is 110 respondents with a consecutive sampling technique. Data collection using medical records and statistical tests using independent sample t-test.Results: Analyzing the weight gain in the contraceptive injection acceptor that is the average injection of 1-month experienced of 2.16 kilograms and injections of 3-months experienced of 2.95 kilograms. The results of the independent t-test with a significance value of 0.039 (p <0.05).Conclusion: There was a significant difference in weight gain between 1-month and 3-months injective contraception acceptors, with the highest increase occurred in 3-months, injective contraceptive acceptors.